Decolonial position in the formation of the term - Aliszhan, С.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article explores the decolonial position in Kazakh term formation, emphasizing linguistic decolonization as a means of restoring national identity. The concept of decoloniality seeks to reclaim original values in terminology, ensuring the communicative function of language in scientific discourse. Without this orientation, national scientific understanding cannot fully develop. The article clarifies the decolonial approach to term formation and examines linguistic mechanisms lost due to political influences. It also highlights the legacy of Alash intellectuals, particularly A. Baitursynuly, in shaping terminology. A decolonial stance in term formation fosters scientific concepts in the native language, contributing to the development of Kazakh scientific consciousness and expanding the state language’s application. Using scientific sources, the article analyzes the negative impact of post-Soviet ideology on Kazakh scientific discourse and highlights new trends in terminology since independence. It presents literature on linguistic decolonization and terminology, offering insights into emerging directions in term formation and enhancing linguistic competence across various fields.